2003
DOI: 10.1081/jas-120018706
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of Swimming in Asthma: Effect of a Session of Swimming Lessons on Symptoms and PFTs with Review of the Literature

Abstract: A study involving eight children with moderate persistent asthma was undertaken to determine whether standard swimming lessons improved symptoms and pulmonary function tests (PFTs) in asthmatic children. Five children ages 7-12 years old with moderate persistent asthma were randomized to a swimming lesson group (5- to 6-week session) and three to a control group. Both groups completed pre- and poststudy period PFTs and symptom questionnaires. Swimming lessons did not produce a significant change in asthma symp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
70
0
11

Year Published

2005
2005
2013
2013

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(86 citation statements)
references
References 34 publications
1
70
0
11
Order By: Relevance
“…However, the research regarding the effects of exercise training on asthmatics is sparse and there has continually been a self-inflicted restriction of physical and sporting activities in asthmatics. This is so despite clinicians having advised that exercise can take place when asthmatics use beta-agonists prior to exercise, avoid conditions that are likely to produce exercise-induced asthma and participate in swimming which is deemed less asthmogenic than other forms of exercise [1,2]. Asthmatics can safely and successfully exercise with the correct interventions [3] as seen when 41 medals were won (albeit controversially due to the stimulant effects of asthma medication) at the 1984 Olympic Games by American athletes with a history of asthma or exercise-induced asthma (EIA) in high-respiratory events such as cycling and swimming [4].…”
Section: Introductionmentioning
confidence: 99%
“…However, the research regarding the effects of exercise training on asthmatics is sparse and there has continually been a self-inflicted restriction of physical and sporting activities in asthmatics. This is so despite clinicians having advised that exercise can take place when asthmatics use beta-agonists prior to exercise, avoid conditions that are likely to produce exercise-induced asthma and participate in swimming which is deemed less asthmogenic than other forms of exercise [1,2]. Asthmatics can safely and successfully exercise with the correct interventions [3] as seen when 41 medals were won (albeit controversially due to the stimulant effects of asthma medication) at the 1984 Olympic Games by American athletes with a history of asthma or exercise-induced asthma (EIA) in high-respiratory events such as cycling and swimming [4].…”
Section: Introductionmentioning
confidence: 99%
“…14 Some authors found no beneficial effect of swimming in asthmatic children, however. Weisgerber et al, 15 for example, reported that swimming lessons did not produce a significant change in symptoms or pulmonary function test results in children with moderate persistent asthma.…”
Section: Effects Of Swimming In Asthmatic Patientsmentioning
confidence: 99%
“…This fact was addressed at length in a Thorax editorial 25 While some studies have shown beneficial effects of swimming on pulmonary function test parameters, 11,15 others have failed to show any such effect. 3,10,13,29 However, none of these studies used BHR assessment as a followup tool. BHR must be assessed, especially in studies that evaluate response to asthma treatment over time.…”
Section: Allergy Skin Testingmentioning
confidence: 99%